2021
DOI: 10.1183/13993003.00768-2021
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting adherence with treatment advice in a clinical trial of patients with severe asthma

Abstract: BackgroundUnderstanding why patients with severe asthma do not follow healthcare provider (HCP) advice to adjust treatment is critical to achieving personalised disease management.MethodsWe reviewed patient choice to follow HCP advice to adjust asthma treatment in a randomised, controlled, single-blind (study participant), multi-centre, parallel group 48-week clinical study comparing biomarker directed treatment adjustment to standard care in severe asthma.ResultsOf 1572 treatment advisories (301 participants)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
(23 reference statements)
0
9
0
1
Order By: Relevance
“…11 The refractory asthma stratification programme demonstrated that patients from ethnic minority groups were less likely to adhere to treatment advised in the clinical trial and had higher asthma exacerbations than white patients. 12 Current guidelines for the use of biologics in asthma are based on data from translational research and clinical trials conducted mainly in white populations from HICs. Whilst ethnicity is considered to be mainly a social construct, a recent case-control study from the USA involving African American, Mexican and Puerto Rican children highlighted key differences in blood parameters influencing eligibility for biologic therapies.…”
Section: Allergic Rhinitis and Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…11 The refractory asthma stratification programme demonstrated that patients from ethnic minority groups were less likely to adhere to treatment advised in the clinical trial and had higher asthma exacerbations than white patients. 12 Current guidelines for the use of biologics in asthma are based on data from translational research and clinical trials conducted mainly in white populations from HICs. Whilst ethnicity is considered to be mainly a social construct, a recent case-control study from the USA involving African American, Mexican and Puerto Rican children highlighted key differences in blood parameters influencing eligibility for biologic therapies.…”
Section: Allergic Rhinitis and Asthmamentioning
confidence: 99%
“…Data from the UK severe asthma registry and the optimum patient care research database showed that, as compared to the white population, the ethnic minority population was more atopic, expressed higher type 2 inflammation markers and serum total immunoglobulin E (IgE), had lower lung function and worse asthma control 11 . The refractory asthma stratification programme demonstrated that patients from ethnic minority groups were less likely to adhere to treatment advised in the clinical trial and had higher asthma exacerbations than white patients 12 . Current guidelines for the use of biologics in asthma are based on data from translational research and clinical trials conducted mainly in white populations from HICs.…”
Section: Allergic Diseases In Ethnic Minority Population In Hics—disp...mentioning
confidence: 99%
“…36 Higher adherence would be expected in these centers, yet patient outcomes vary considerably across different sites, indicating that multidisciplinary teams alone do not increase adherence. 37 This information highlights the importance of healthcare services in delivering the best quality healthcare for patients with asthma.…”
Section: Causes Of Poor Treatment Adherencementioning
confidence: 99%
“…According to Busby et al, 16 up to 30% of patients did not reduce their OCS doses when advised to do so, even though they voluntarily and knowingly enrolled in an algorithm-driven reduction trial. Strikingly, the adherence levels were largely dependent on the recruiting centre, suggesting that the local culture and the manner in which healthcare professionals present the advice are important factors.…”
mentioning
confidence: 99%
“…Strikingly, the adherence levels were largely dependent on the recruiting centre, suggesting that the local culture and the manner in which healthcare professionals present the advice are important factors. 16 This may translate into even lower adherence to advice in a real-world clinical setting.…”
mentioning
confidence: 99%